Time-dependent springback of a commercially pure titanium sheet. (2017) - Hama, Takayuki; Sakai, Takeyuki; Fujisaki, Yusuke; Fujimoto, Hitoshi; Takuda, Hirohiko
Abstract: Time-dependent springback of a commercially pure titanium sheet was investigated experimentally from the viewpoints of strain rate, holding time at the bottom dead center before unloading, and elapsed time after unloading. A draw-bending test showed that the amount of springback decreased linearly with the holding time before unloading when plotted on logarithmic scale and increased with the elapsed time after unloading. To investigate the mechanism of these results, stress relaxation and creep tests were conducted. The variation of the amount of springback with the holding time corresponded well with that of the stress during stress relaxation. On the other hand, the in-plane anisotropy in the evolution of the amount of springback with the elapsed time did not correspond with that of creep strain. The mechanism of the in-plane anisotropy in the elapsed-time dependency was discussed in terms of the stress relaxation and creep behaviors.